2017
DOI: 10.1515/pjvs-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

A systemic review of existing serological possibilities to diagnose canine osteoarthritis with a particular focus on extracellular matrix proteoglycans and protein

Abstract: Extra-cellular matrix (ECM) components are important and their stabilization is significant in maintaining normal healthy joint environment. In osteoarthritis (OA), ECM components are altered and indicate disease progression. The joint ECM is composed of proteoglycans (aggrecan, perlecan, inter α-trypsin inhibitor), glycoproteins (fibronectin, lubricin, COMP) and collagen types (most abundantly collagen type II) which represent structural and functional transformation during disease advancement. ECM investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
6
2
Order By: Relevance
“…Alternatively, body fluid proteins are being evaluated for their capabilities in screening for, diagnosing, staging, and monitoring the development and progression of OA in CHD and other joint disorders. To date, OA research using protein biomarkers has primarily focused on breakdown products of articular cartilage in serum and/or synovial fluid . No significant differences were found in CTX‐II concentrations in synovial fluid between controls and dogs affected with OA, while CTX‐II levels in the urine of dysplastic dogs were significantly lower than non‐dysplastic dogs in the present study.…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…Alternatively, body fluid proteins are being evaluated for their capabilities in screening for, diagnosing, staging, and monitoring the development and progression of OA in CHD and other joint disorders. To date, OA research using protein biomarkers has primarily focused on breakdown products of articular cartilage in serum and/or synovial fluid . No significant differences were found in CTX‐II concentrations in synovial fluid between controls and dogs affected with OA, while CTX‐II levels in the urine of dysplastic dogs were significantly lower than non‐dysplastic dogs in the present study.…”
Section: Discussioncontrasting
confidence: 61%
“…To date, OA research using protein biomarkers has primarily focused on breakdown products of articular cartilage in serum and/or synovial fluid. 14,23,[32][33][34] No significant differences were found in CTX-II concentrations in synovial fluid between controls and dogs affected with OA, 35 while CTX-II levels in the urine of dysplastic dogs were significantly lower than non-dysplastic dogs in the present study. Another study showed significantly increased levels of TIMP-1, and no significant differences in MMP3 levels in serum and synovial fluid of dogs with CHD compared to non-dysplastic controls.…”
Section: Figurecontrasting
confidence: 67%
See 3 more Smart Citations